1999
DOI: 10.1097/00006123-199907000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brain Ventricular Shape on Periventricular Biomechanics: A Finite-element Analysis

Abstract: The distribution of periventricular edema in acute hydrocephalus is a result not only of increased intraventricular pressure but also of ventricular geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…5,30 Despite the advances reported in these studies, the models used omitted other important geometrical details, such as sulci. Additionally, there has been no attempt to investigate the effect of the degree of ventricular deformation on the biomechanical changes in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5,30 Despite the advances reported in these studies, the models used omitted other important geometrical details, such as sulci. Additionally, there has been no attempt to investigate the effect of the degree of ventricular deformation on the biomechanical changes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous FE simulation study suggested that geometrical characteristics may play a major role in PVL in hydrocephalus. 30 In that study, Peña et al found that the distribution of PVL is affected by ventricular geometry, and considered their findings to be evidence supporting the extravasation theory. In contrast, the present study further investigated the effects of the degree of structural deformation, and the results led to opposite conclusions.…”
Section: Influence Of Geometrical Characteristics Of the Hydrocephalimentioning
confidence: 93%
See 3 more Smart Citations